Development of digital competence of university teachers and teaching staff - Aksar A. Eltemerov (RUDN Journal of Informatization in Education)
Formulation of the problem. Currently, digital technologies are an integral part of all social institutions. This global digitalization of the human living environment changes the very paradigm of thinking of the new generation. A modern teacher needs to meet the new demands of the sociocultural environment. This determines the relevance of developing scientifically based models for the formation and assessment of the level of digital competence of teachers. Methodology . The main method chosen is the analysis of the results of a survey of Russian university teachers about the problem of digital competence of representatives of the teaching staff and other employees of universities. A bibliometric analysis of open sources was carried out on the topic of developing digital competencies of university teachers and monitoring of scientific publications using the keywords: “digitalization”, “digital technologies”, “digital competence of a teacher”. Results . The study displays the results of a survey on the presence of incompetent representatives from among the teaching staff and from among other employees (employees) of departments of Russian universities, as well as the results of a survey on the compliance of the level of material and technical equipment of universities with the needs of the modern digital society. A model for assessing the level of digital competence of university teaching staff is proposed. Conclusion . In the process of research work, the need to design the process of developing digital competence, first of all, of the teaching staff and, secondly, of other workers (employees) of university departments was confirmed. To solve the problem under study, it is proposed to structure the digital training model into categories and determine the level of required digital competence for each category.